Seasonal Variation in Family Member Perceptions of Physician Competence in the Intensive Care Unit: Findings From One Academic Medical Center. (April 2015) - Stevens, Jennifer P.; Kachniarz, Bart; O'Reilly, Kristin; Howell, Michael D.
Abstract : Purpose: Researchers have found mixed results about the risk to patient safety in July, when newly minted physicians enter U.S. hospitals to begin their clinical training, the so-called "July effect." However, patient and family satisfaction and perception of physician competence during summer months remain unknown. Method: The authors conducted a retrospective observational cohort study of 815 family members of adult intensive care unit (ICU) patients who completed the Family Satisfaction with Care in the Intensive Care Unit instrument from eight ICUs at Beth Israel Deaconess Medical Center, Boston, Massachusetts, between April 2008 and June 2011. The association of ICU care in the summer months (July–September) versus other seasons and family perception of physician competence was examined in univariable and multivariable analyses. Results: A greater proportion of family members described physicians as competent in summer months as compared with winter months (odds ratio [OR] 1.9; 95% confidence interval [CI] 1.2–3.0; P = .003). After adjustment for patient and proxy demographics, severity of illness, comorbidities, and features of the admission in a multivariable model, seasonal variation of family perception of physician competence persisted (summer versus winter, OR of judging physicians competent 2.4; 95% CI 1.3–4.4; P = .004). Conclusions: Seasonal variation exists in family perception of physician competence in the ICU, but opposite to the "July effect." The reasons for this variation are not well understood. Further research is necessary to explore the role of senior provider involvement, trainee factors, system factors such as handoffs, or other possible contributors. Abstract : Supplemental Digital Content is available in the text.